Utility of transient elastography in the non‐invasive evaluation of cystic fibrosis liver disease. (22nd February 2013) - Kitson, Matthew T.; Kemp, William W.; Iser, David M.; Paul, Eldho; Wilson, John W.; Roberts, Stuart K.
Abstract Background Liver disease frequently complicates cystic fibrosis (CF), with CF liver disease (CFLD) a leading cause of death. Liver biopsy is rarely performed because of the patchy nature of the disease. Transient elastography can reliably stage liver fibrosis via liver stiffness measurement (LSM). Aims To evaluate LSM as a diagnostic tool in adults with CFLD. Methods Fifty adult patients with CF were prospectively studied: 25 with CFLD and 25 without CFLD. The presence of CFLD and portal hypertension (PHT) was assessed according to strict established criteria based on serial biochemistry and imaging. All patients underwent LSM; APRI, Hepascore® and Forns score were calculated. Results Median LSM was higher in those with CFLD [8.1 kPa (IQR 6.8–9.5) vs. 5.0 kPa (IQR 4.1–5.6); P < 0.001]. On multivariate analysis, LSM was the only variable associated with CFLD (OR 2.74, 95% CI 1.53–4.89; P = 0.001). AUROC for LSM predicting CFLD was 0.87 (95% CI 0.77–0.98) and an LSM ≥6.8 kPa predicted CFLD with 76.0% sensitivity and 92.0% specificity. Median LSM was higher in those with PHT [15.7 kPa (IQR 9.2–17.2) vs. 5.4 kPa (IQR 4.3–6.8); P < 0.001]. The AUROC for LSM predicting the presence of PHT was 0.96 (95% CI 0.92–1.00). An LSM cut‐off of ≥8.9 kPa predicted the presence of PHT with 87.5% sensitivity, 90.5% specificity, 63.6% positive predictive value and 92.9% negative predictive value. Conclusions LSM is an accurate and reliable non‐invasive tool in assessing CFLD and PHT. An LSM ≥6.8 kPa is highly suggestive of CFLD and an LSM <8.9 kPa reliably excludes PHT.